MCL and Mincle: C-Type Lectin Receptors That Sense Damaged Self and Pathogen-Associated Molecular Patterns - Richardson, Mark B.; Williams, Spencer J. (Frontiers in Immunology, 2014)
MCL (macrophage C-type lectin) and mincle (macrophage inducible C-type lectin) comprise part of an extensive repertoire of pattern recognition receptors with the ability to sense damage associated and pathogen associated molecular patterns. In this review we cover the discovery and molecular characterization of these C-type lectin receptors, and highlight recent advances in the understanding of their roles in orchestrating the response of the immune system to bacterial and fungal infection, and damaged self. We also discuss the identification and structure-activity relationships of activating ligands, particularly trehalose dimycolate (TDM) and related mycobacterial glycolipids, which have significant potential in the development of TH1/TH17 vaccination strategies.